The Effect of Problem-Based Learning and Students' Understanding of Physics Concepts On The Topic of The Doppler Effect - Jamaludin Jamaludin; Izaak Hendrik Wenno; John Rafafy Batlolona (STKIP Singkawang, 2022)
Understanding the concept is one of the essential needs teachers pursue in improving student competence in the current era of openness. One of the learning models that can sharpen and encourage students' understanding of physics concepts is problem-based learning (PBL). Heretofore, research related to understanding concepts with PBL in understanding the Doppler effect material in depth is still minimal. Therefore, through this research, an exploration was carried out to determine the extent to which students' understanding of the Doppler effect material was carried out. The purpose of this study was to analyze the effect of PBL on students' conceptual understanding. This type of research is experimental with a total of 58 students. Both the experimental and the control classes were in class 11 of the science major of Christian Senior High School Ambon. The research procedure was a conceptual understanding test, which was carried out during the research process. The data analysis used was an independent sample T-test. The results showed that the average value of PBL class students' learning outcomes related to students' conceptual understanding was higher than conventional classes. It shows that PBL improve students' conceptual understanding of the Doppler effect material.